DPP-4 Inhibitors in the Prevention/Treatment of Pulmonary Fibrosis, Heart and Kidney Injury Caused by COVID-19—A Therapeutic Approach of Choice in Type 2 Diabetic Patients? - Smelcerovic, Andrija; Kocic, Gordana; Gajic, Mihajlo; Tomovic, Katarina; Djordjevic, Vukica; Stankovic-Djordjevic, Dobrila; Anderluh, Marko (Frontiers in Pharmacology, 2020)
Since the outbreak of SARS-CoV-2 virus more than 12 500 000 cases have been reported worldwide. Patients suffering from diabetes and other comorbidities are particularly susceptible to severe forms of the COVID-19 that might result in chronic complications following recovery. Dipeptidyl peptidase-4 inhibitors exert beneficial effects in prevention/treatment of pulmonary fibrosis, heart, and kidney injury, and since they may be a long-term consequence caused by COVID-19, it is reasonable to expect that DPP-4 inhibitors might be beneficial in alleviating long-term consequences of COVID-19. With that in mind, we would like to voice our concerns over chronic implications following recovery from COVID-19 especially in diabetic, but also in non-diabetic patients, and to indicate that some preventive measures could be undertaken by application of DPP-4 inhibitors